Design and Development of Bismuth Ferrite Based Environmental Friendly Multiferroic for Devices. (2019) - Kumar, Nitin; Shukla, Alok; Kumar, Nripesh; Choudhary, R N P
Abstract: Recently, researches are mainly focussed on the development of eco-friendly materials for multifunctional devices. In the present communication, synthesis and detailed characterization of Bi(Ni0.30 Ti0.30 Fe0.40 )O3 multiferroic material has been reported. This compound has been synthesized via a cost-effective (solid-state reaction or mixed oxide) technique in air atmosphere. Based on the analysis of X-ray diffraction data (collected on powder sample) crystal system, unit cell dimension and crystallite (particle) size of material were determined. The calculated particle size of the material is in the range of 28 to 52 nm. Analysis of the field emission scanning electron micrograph (FE-SEM) depicts uniform distribution of grains of varying dimension. Furthermore, the correlation between dielectric and impedance parameters is established using experimental data collected by a phase sensitive multimeter at various temperature and frequency. The impedance spectroscopic studies are performed in a broad range of temperature (300–780 K) and ac field frequencies (10 3 –10 6 Hz). As a result, the addition of Ni (nickel) and Ti (titanium) at the Fe (iron) site of BiFeO3 enhances electrical as well as multiferroic properties of the material.